2018
DOI: 10.3389/fpls.2018.01577
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Genetic Architecture of Melon Chilling Tolerance at the Seedling Stage by Association Mapping and Identification of the Elite Alleles

Abstract: Low temperature is an important abiotic stress that negatively affects morphological growth and fruit development in melon (Cucumis melo L.). Chilling stress at the seedling stage causes seedling injury and poor stand establishment, prolonging vegetative growth and delaying fruit harvest. In this study, association mapping was performed for chilling tolerance at the seedling stage on an expanded melon core collection containing 212 diverse accessions by 272 SSRs and 27 CAPSs. Chilling tolerance of the melon se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Considering that equivalent pathways might be regulated by ARFs in melon, it is reasonable to assume that the down-regulation of the TAS3-derived tasiRNA observed in cold-exposed and HSVd-infected plants might be related to the developmental alterations observed in plants growing under these adverse environmental conditions, mainly characterized by delayed growth (Hataya et al 2017, Hou et al 2018. However, we cannot exclude the possibility that changes in the ARF levels observed in cold exposed and HSVd-infected plants may be also modulated, at least in part, by and stress-related increasing in its transcription level, resembling the previously observed in divers plant species such as rice (Jain and Khurana, 2009), sorghum (Wang et al, 2010), banana (Hu et al, 2015) and pepper .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that equivalent pathways might be regulated by ARFs in melon, it is reasonable to assume that the down-regulation of the TAS3-derived tasiRNA observed in cold-exposed and HSVd-infected plants might be related to the developmental alterations observed in plants growing under these adverse environmental conditions, mainly characterized by delayed growth (Hataya et al 2017, Hou et al 2018. However, we cannot exclude the possibility that changes in the ARF levels observed in cold exposed and HSVd-infected plants may be also modulated, at least in part, by and stress-related increasing in its transcription level, resembling the previously observed in divers plant species such as rice (Jain and Khurana, 2009), sorghum (Wang et al, 2010), banana (Hu et al, 2015) and pepper .…”
Section: Discussionmentioning
confidence: 99%
“…It also identified two SNPs on chromosome 1 as being responsible for the PA phenotype. GWAS was used to map other important agronomic traits in watermelon, melon and cucumber ( Nimmakayala et al, 2016 ; Yagcioglu et al, 2016 ; Dou et al, 2018a ; Dou et al, 2018b ; Hou et al, 2018 ; Wang et al, 2018 ; Bo et al, 2019b ; Bo et al, 2019a ; Oren et al, 2019 ). The major sex-determining gene for monoecy/andromonoecy in melon ( CmACS7 ) was also successfully detected using the GWAS approach ( Gur et al, 2017 ; Zhang H. et al, 2019 ), but so far no other andromonoecy locus had been found in cucurbits.…”
Section: Discussionmentioning
confidence: 99%
“…Two-leaf seedlings were used in the cold treatment experiments. Seedlings with developmental uniformity were treated in a climatic chamber at 4°C for 48 h, followed by recovery at normal conditions for 72 h. The chilling injury class was then determined by scoring the phenotype of the first true leaf, and the chilling injury index (CII) was calculated according to Hou et al [ 18 ], although the number of injury classes was increased from five to nine. Three biological replicates were performed for CII and each replicate contained 15 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with model plants such as Arabidopsis thaliana , rice, and tomato, research into cold tolerance in melon lags behind. CMCT505_Chr.1 was identified as a key locus that controls cold tolerance in melon in a genome-wide association study (GWAS), but it was not genetically dissected [ 18 ]. At present, no QTL or gene related to low temperature tolerance has been cloned using forward genetics in melon.…”
Section: Introductionmentioning
confidence: 99%